2017
DOI: 10.1111/gcb.13941
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of growing‐season precipitation peaks decrease soil respiration in a semiarid grassland

Abstract: Changing precipitation regimes could have profound influences on carbon (C) cycle in the biosphere. However, how soil C release from terrestrial ecosystems responds to changing seasonal distribution of precipitation remains unclear. A field experiment was conducted for 4 years (2013-2016) to examine the effects of altered precipitation distributions in the growing season on soil respiration in a temperate steppe in the Mongolian Plateau. Over the 4 years, both advanced and delayed precipitation peaks suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 57 publications
2
46
0
1
Order By: Relevance
“…On average, our results showed that warming, elevated CO 2 , N fertilization, and increased precipitation significantly increased APCP, BPCP, SCP, and Rs, while drought exhibited negative effects on those variables (Figure ). Drought generally impedes plant growth due to the reduction of canopy photosynthesis and nutrient uptake from soil by decreased SM and relative humidity in grassland ecosystems (Davidson & Janssens, ; Knapp & Smith, ; Ru, Zhou, Hui, Zheng, & Wan, ). The decreased canopy photosynthesis induced by drought may also reduce root biomass due to depressed supply of photosynthetic products to roots, resulting in decreased microbial biomass, a smaller SCP, and lower Rs (Knapp & Smith, ; Liu et al, ; van Groenigen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On average, our results showed that warming, elevated CO 2 , N fertilization, and increased precipitation significantly increased APCP, BPCP, SCP, and Rs, while drought exhibited negative effects on those variables (Figure ). Drought generally impedes plant growth due to the reduction of canopy photosynthesis and nutrient uptake from soil by decreased SM and relative humidity in grassland ecosystems (Davidson & Janssens, ; Knapp & Smith, ; Ru, Zhou, Hui, Zheng, & Wan, ). The decreased canopy photosynthesis induced by drought may also reduce root biomass due to depressed supply of photosynthetic products to roots, resulting in decreased microbial biomass, a smaller SCP, and lower Rs (Knapp & Smith, ; Liu et al, ; van Groenigen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower soil water contents in the growing season may impede canopy photosynthesis and then suppress root activity (e.g. water and nutrient uptake, Ru et al, 2018). Decreased transport of assimilated C towards the rhizosphere could also suppress soil microbial biomass F I G U R E 5 Effects of drought on relationships between soil temperature and autotrophic respiration (Ra, A), heterotrophic respiration (Rh, B), and soil respiration (Rs, C), relationships between volumetric soil moisture and Ra (D), Rh (E) and Rs (F).…”
Section: Root Biomass and Microbial Community Regulate The Responsementioning
confidence: 99%
“…Model simulations and field experiments both indicate that drought decreases soil water availability (Ru et al, 2018) and influences Rs by modifying roots and soil microbial communities (Luo & Zhou, 2006).…”
mentioning
confidence: 99%
“…Our planet has experienced drastic global climate change, with accelerating warming and shifting precipitation regimes, in past decades [1][2][3]. Climate change affects ecosystem services and functions by altering vegetation phenology, plant community composition, and biogeochemical cycles [4][5][6]. For example, semiarid grasslands in East Africa are threatened in the context of increasing climate variability and climate extremes, especially in terms of ecosystem productivity and stability [7].…”
Section: Introductionmentioning
confidence: 99%